IQD1 Involvement in Hormonal Signaling and General Defense Responses Against Botrytis cinerea - Barda, Omer; Levy, Maggie (Frontiers in Plant Science, 2022)
IQ Domain 1 (IQD1) is a novel Arabidopsis thaliana calmodulin-binding protein , which was found to be a positive regulator of glucosinolate (GS) accumulation and plant defense responses against insects. We demonstrate here that the IQD1 overexpressing line (IQD1OXP) was also more resistant also to the necrotrophic fungus Botrytis cinerea, whereas an IQD1 knockout line (iqd1-1) was much more sensitive. Furthermore, we showed that IQD1 is up-regulated by jasmonic acid (JA) and downregulated by salicylic acid (SA). A comparison of whole transcriptome expression between iqd1-1 and wild type plants revealed a substantial downregulation of genes involved in plant defense and hormone regulation. Further examination revealed a marked reduction of SA and increases in the levels of ethylene, JA and abscisic acid response genes in the iqd1-1 line. Moreover, quantification of SA, JA and abscisic acids in IQD1OXP and iqd1-1 lines relative to the wild type, showed a significant reduction in endogenous JA levels in the knockout line, simultaneously with increased SA levels. Relations between IQD1OXP and mutants defective in plant-hormone response indicated that IQD1 cannot rescue the absence of NPR1 or impaired SA accumulation in the NahG line. IQD1 cannot rescue ein2 or eto1 mutations connected to the ethylene pathway involved in both defense responses against B. cinerea and in regulating GS accumulation. Furthermore, IQD1cannot rescue the aos, coi1 or jar1 mutations, all involved in the defense response against B. cinerea, and it depends on JAR1 to control indole glucosinolate accumulation. We also found that in the B. cinerea, which infected the iqd1-1 mutant, the most abundant upregulated group of proteins is involved in the degradation of complex carbohydrates, as correlated with the sensitivity of this mutant. In summary, our results suggest that IQD1 is an important A. thaliana defensive protein against B. cinerea that is integrated into several important pathways, such as those involved in plant defense and hormone responses.